2021
DOI: 10.1186/s13075-021-02682-w
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of lncRNA IL21-AS1 in interleukin-2 and T follicular regulatory cell activation in systemic lupus erythematosus

Abstract: Background The single nucleotide polymorphism (SNP) rs62324212, located in IL21 antisense RNA 1 (IL21-AS1), has been identified as a genetic risk variant associated with systemic lupus erythematosus (SLE). We aimed to probe the characteristics of IL21-AS1 and explore its clinical relevance focusing on T helper subsets and disease activity in patients with SLE. Methods rs62324212 genotyping was determined using allelic discrimination by quantitative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…In subsequent studies, researchers have found that IL‐2 plays a pivotal role in maintaining the suppression function of Tfrs. 245 , 246 , 247 When serum IL‐2 levels were reduced in patients with SLE, the proportion of CD4 + CXCR5 + FOXP3 – PD‐1 high Tfhs was increased, whereas the proportion of CD4 + CXCR5 + CD45RA – FOXP3 high Tfrs was decreased. 245 However, stimulation with an exogenous low dose of IL‐2 could restore the function of Tfrs and converse Tfhs to Tfrs by regulation of FOXP3 and BCL6 through histone modification.…”
Section: Treg Subsets In Autoimmune Diseasementioning
confidence: 99%
“…In subsequent studies, researchers have found that IL‐2 plays a pivotal role in maintaining the suppression function of Tfrs. 245 , 246 , 247 When serum IL‐2 levels were reduced in patients with SLE, the proportion of CD4 + CXCR5 + FOXP3 – PD‐1 high Tfhs was increased, whereas the proportion of CD4 + CXCR5 + CD45RA – FOXP3 high Tfrs was decreased. 245 However, stimulation with an exogenous low dose of IL‐2 could restore the function of Tfrs and converse Tfhs to Tfrs by regulation of FOXP3 and BCL6 through histone modification.…”
Section: Treg Subsets In Autoimmune Diseasementioning
confidence: 99%
“…SNP-PCR was performed according to the instructions supplied by the manufacturer to determine the genotypes of rs1893592-A/C, as described previously [ 16 ]. On a Step One Plus system (Applied Biosystems), PCR was performed in 10 μL of reaction volume containing 1 μL of genomic DNA (20 ng/μL) from 14 RA patients (male to female 4:10), 5 μL of TaqMan Universal PCR Master Mix, 0.25 μL of VIC/FAM-labeled probe (200 nM), and 3.75 μL of double-distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a study revealed the possible involvement of Interleukin-21 antisense RNA 1 (IL21-AS1) in the dysregulated IL-2-Tfr cell axis in patients with SLE. 84 IL21-AS1 was identified its expression reduced in both PBMCs and CD4 + T cells of SLE. Besides, the expression of IL21-AS1 in PBMCs of SLE patients is positively correlated with the expression of IL-2.…”
Section: Il21-as1mentioning
confidence: 95%